Retrospective analysis of maternal mortality: a paradigm shift from 2010 to 2020 - Kempaiah, Sujani; ., Urvashi; ., Mamatha; Fernandes, Jessica Celina; Sivasambu, Gayatri Devi; Azmathulla, Shaziya; Shivashankar, Shruthi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Maternal mortality is attributed usually to complications that generally occur during or around labour and these are mostly preventable through proper understanding, diagnosis and management of labour complications. The quality of health services women receive during pregnancy, intranatal and postnatal periods are crucial for the survival and well-being of the mother and her newborn baby. The objective was to analyse the changing trends in maternal mortality occurring over a decade, to assess factors associated with maternal mortality and propose effective interventions in preventing such mortality. Methods: It was a retrospective study to analyse maternal mortality between January 2010 and January 2020 in Ramaiah medical college hospital. Data was collected the institutional medical and delivery records and patient details regarding obstetric history, pre-existing comorbidities, cause of death, interventions done was noted and review of maternal mortality was done. Results: The maternal mortality in the present study was 432.73/1 lakh live births. There were 57 maternal deaths in the study period. Most deaths occurred in the 20-25 age group. 42.10% of deaths occurred ninety six hours after admission. Sepsis (42.1%), hypertensive disorders (12.30%) and haemorrhage (10.5%) are the most common direct causes of maternal death. Post-operative and post abortal sepsis, ARDS, cardiogenic shock, pulmonary embolism and AFLP are the other direct causes. Hypertensive disorders (9.64%) and haemorrhage (19.5) is the two leading indirect causes of maternal deaths. Conclusions: Maternal health services should move beyond the focus on emergency obstetric care, to a broader approach that encompasses preventive and early interventions and integration with existing services. Most of the maternal deaths can be prevented if the high risk antenatal women are identified earlier and referred to the tertiary centre earlier for diagnosis and management.